PERAN DIGITALISASI KOMUNIKASI ANTAR KARYAWAN PT. SENSE INDONESIA DALAM ADAPTASI NEW NORMAL - Siti Nur Afifah Azwindhita (2022)
This research aims to determine the role of digitalization in communication between Sense Indonesia employees in adapting to the new normal and to find out the forms of obstacles in digitizing communication faced by Sense Indonesia in adapting to the new normal. The policy of working from home or Work-From-Home (WFH) was implemented to break the chain of the spread of the Covid-19 outbreak, which suddenly became an interesting phenomenon for the researcher. This research uses qualitative research with a case study approach. The data collection technique used in-depth interviews with six informants and focused observations. The data analysis technique used by the researcher is a data analysis technique according to Moleong which consists of three stages, data reduction, data display, and conclusions and data verification. This study uses the theory of Computer Mediated Communication (CMC). The results of this study found that PT. Sense Indonesia experienced a change in communication style to 100% digitalization. In maximizing the digitalization process, this communication has several obstacles when adapting in this New Normal period such as miscommunication from both internal and external parties, and infrastructure from external parties consisting of (internet network, devices and technology readiness). Regulations at PT. Sense Indonesia is also always updated to make it easier for the internal team to minimize the obstacles that occur.